Role of thermal energy storage for enhancing thermal performance of evacuated tube with compound parabolic concentrator collector. (23rd December 2020) - Christopher, S.; Kumaresan, V.; Raghavan, K.S.
Summary: Evacuated tube (ET) solar collectors are utilized in all climatic conditions for harnessing solar energy. This work aims to investigate thermal performance of ET with compound parabolic concentrator collector, integrated to a multiple phase change material‐based thermal energy storage (TES) system. The phase change material (PCM) have been selected depending on the degree of stratification in sensible heat storage configuration under constant heat load conditions. The charging experiments have been performed under three different TES configurations viz. sensible heat storage, three ("Case 1") and five ("Case 2") PCMs, using water as the heat transfer augmenting the energy storage by 41% than the sensible heat storage. A higher stratification number in "Case 2" reveals the significance of multiple PCMs in improving the charging efficiency of TES system. Cascaded arrangement of PCMs facilitates the supply of HTF at lower temperature to the collector resulting with an increase in useful heat energy gained. The instantaneous thermal efficiency of collector with "Case 2" is as high as 58%, storing 27 MJ d −1 . Use of ET‐CPC and TES system with cascaded arrangement of PCMs finds potential application in water heating system. Abstract : This work proposes a novel phase change material configuration in thermal energy storage system for improving the thermal efficiency of evacuated tube‐compound parabolic concentrator collector. Five PCMs configuration stores 41% and 12% more energy than three PCMs and sensible heat storage configurations. With the cascaded arrangement of PCMs, heat transfer fluid is supplied at low temperatures to the collector, augmenting the overall performance and making it a promising method for solar based water heating applications.